Manufacturing method of laminated film and strain sensor

The laminated film with a thin resistive layer and controlled dimensional changes addresses the issues of temperature resistance coefficient fluctuations and crack formation in strain gauges, enhancing their accuracy and reliability in humid and heat environments.

JP7659380B2Active Publication Date: 2025-04-09NITTO DENKO CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020182136
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-30
Publication Date
2025-04-09
Estimated Expiration
2040-10-30

AI Technical Summary

Technical Problem

Conventional strain gauges face challenges in suppressing fluctuations in the temperature resistance coefficient due to storage in humid and heat environments, and are prone to crack formation, which affects their ability to sense distortion accurately.

Method used

A laminated film with an insulating substrate film and a resistive layer, where the resistive layer is 150 nm or less in thickness, and the film is cut to specific dimensions and subjected to thermal and humidity testing to ensure dimensional change rates of 0.025% or less, thereby suppressing temperature resistance coefficient fluctuations and crack formation.

Benefits of technology

The solution effectively suppresses fluctuations in the temperature resistance coefficient and prevents crack formation in strain sensors, ensuring accurate distortion sensing even in humid and heat environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659380000002
    Figure 0007659380000002
  • Figure 0007659380000003
    Figure 0007659380000003
  • Figure 0007659380000004
    Figure 0007659380000004
Patent Text Reader

Abstract

To provide a method for manufacturing a laminate film and a strain sensor in which variations in a coefficient of temperature resistance by storage in a wet heat environment are suppressed and generation of cracks is suppressed.SOLUTION: A laminate film 1 has an insulating base material film 2, and a resistance layer 3 in this order in a thickness direction. A thickness of the resistance layer 3 is 150 nm or less. The laminate film 1 is cut into lengths in each of a first direction and a second direction that are orthogonal to each other of 15 mm and 5 mm, and after both ends in the first direction of a sample have been pulled with a force of 49 mN / 5 mm in an atmosphere at 85°C and 85%RH for 4 hours, each absolute value of a dimensional change rate in each of the first direction and the second direction is 0.025% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminated film and a method for manufacturing a strain sensor. [Background technology]

[0002] 2. Description of the Related Art Conventionally, a strain gauge is known that includes a substrate made of polyimide and a resistor made of chromium nitride formed thereon (see, for example, Patent Document 1 below). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-66312 A Summary of the Invention [Problem to be solved by the invention]

[0004] Therefore, the strain gauge is required to suppress the variation in temperature coefficient of resistance due to storage in a hot and humid environment. However, the strain gauge described in Patent Document 1 has a drawback in that it cannot fully satisfy the above requirement.

[0005] Furthermore, if a crack occurs in the resistor of the strain gauge, there is a problem in that the strain of the test object cannot be sensed.

[0006] The present invention provides a laminated film and a method for producing a strain sensor in which the variation in temperature coefficient of resistance due to storage in a humid and hot environment is suppressed and the generation of cracks is suppressed. [Means for solving the problem]

[0007] The present invention (1) is a laminated film having an insulating base film and a resistive layer in that order in the thickness direction, the resistive layer having a thickness of 150 nm or less, the laminated film being cut to lengths of 15 mm and 5 mm in a first direction and a second direction perpendicular to the thickness direction and perpendicular to each other, and after both ends of the sample in the first direction are pulled with a force of 49 mN / 5 mm in an atmosphere of 85°C and 85% RH for 4 hours, the absolute values ​​of the dimensional change rates in each of the first direction and the second direction are both 0.025% or less.

[0008] In the laminated film of the present invention, the absolute values ​​of the dimensional change rates of the laminated film in the first direction and the second direction are both 0.025% or less, so that the fluctuation of the temperature resistance coefficient due to storage in a humid and hot environment is suppressed. In addition, in the laminated film of the present invention, the thickness of the resistive layer is 150 nm or less, so that the generation of cracks can be suppressed.

[0009] The present invention (2) includes a laminated film comprising an insulating base film and a resistive layer in that order in a thickness direction, the resistive layer having a thickness of 150 nm or less, the base film being cut to have lengths of 15 mm and 5 mm in a first direction and a second direction perpendicular to the thickness direction and perpendicular to each other, and after both ends of the sample in the first direction are pulled with a force of 49 mN / 5 mm in an atmosphere of 85°C and 85% RH for 4 hours, the absolute values ​​of the dimensional change rates in each of the first direction and the second direction are both 0.040% or less.

[0010] In the laminated film of the present invention, the absolute values ​​of the dimensional change rates of the base film in both the first and second directions are 0.040% or less, so that the laminated film is prevented from varying in temperature resistance coefficient due to storage in a humid and hot environment. In addition, in the laminated film of the present invention, the thickness of the resistive layer is 150 nm or less, so that the generation of cracks can be prevented.

[0011] The present invention (3) includes the laminate film according to (1) or (2), in which the resistance layer contains chromium nitride.

[0012] The present invention (4) includes the laminate film according to any one of (1) to (3), in which the base film is polyimide or polyethylene naphthalate.

[0013] The present invention (5) includes a method for producing a strain sensor, comprising patterning the resistance layer in the laminated film according to (1) or (2) to form a strain sensor portion.

[0014] According to the manufacturing method of the present invention, it is possible to manufacture a strain sensor in which the fluctuation of the temperature resistance coefficient due to storage in a humid and hot environment is suppressed and the generation of cracks is suppressed. Effect of the Invention

[0015] The laminated film and the strain sensor manufactured by the strain sensor manufacturing method of the present invention are suppressed in fluctuation of the temperature resistance coefficient due to storage in a humid and hot environment, and the generation of cracks is suppressed. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a cross-sectional view of a laminated film according to one embodiment of the present invention. [Diagram 2] 2A and 2B show a strain sensor in which the resistive layer shown in FIG. 1 is patterned, with FIG. 2A being a cross-sectional view and FIG. 2B being a plan view. [Diagram 3] FIG. 3 is a cross-sectional view of a substrate film that is the subject of measurement of the dimensional change rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] First Embodiment A first embodiment of the laminated film of the present invention will be described with reference to FIG.

[0018] <Laminated film> The laminated film 1 is a film for a strain sensor used in manufacturing a strain sensor 15 (see Figs. 2A and 2B) described later. In other words, the laminated film 1 is an intermediate member for producing the strain sensor 15. However, the laminated film 1 is a device that is distributed as a single component and can be used industrially. The laminated film 1 extends in a planar direction perpendicular to the thickness direction. Specifically, the laminated film 1 includes a base film 2 and a resistive layer 3 in this order toward one side in the thickness direction.

[0019] <Base film> The base film 2 is insulating. The base film 2 forms the other surface in the thickness direction of the laminate film 1. The base film 2 extends in the planar direction.

[0020] The thermal expansion coefficient of the base film 2 at 25°C to 155°C is, in both the first direction and the second direction perpendicular to the thickness direction and perpendicular to each other, for example, 28 ppm / °C or less, preferably 20 ppm / °C or less, more preferably 17 ppm / °C or less, and for example, 1 ppm / °C or more. If the thermal expansion coefficient of the base film 2 is equal to or less than the above upper limit, the absolute value of the dimensional change rate of the laminate film 1 (described later) can be set within a predetermined range. In the examples described later, the thermal expansion coefficient is measured, for example, according to the description of JIS K 7197 (1991).

[0021] The thermal shrinkage of the base film 2 at 200°C is, for example, 0.05% or less, preferably 0.04% or less, more preferably 0.03% or less, particularly preferably 0.02% or less, and is, for example, more than 0%. If the thermal shrinkage of the base film 2 is equal to or less than the upper limit described above, the absolute value of the dimensional change rate of the laminated film 1 (described later) can be kept within a predetermined range. The thermal expansion coefficient is measured according to the description of JIS K 7133 (1999).

[0022] The material of the base film 2 is not particularly limited, and specifically, a material having the above-mentioned range of thermal expansion coefficient and / or thermal shrinkage rate is selected. Examples of the material of the base film 2 include resins such as polyimide (PI) and polyethylene naphthalate (PEN). These can be used alone or in combination. From the viewpoint of obtaining a low thermal expansion coefficient and a low thermal shrinkage rate, PI and PEN are preferable. The base film 2 can be a commercially available product, such as Kapton 200V, Kapton 200EN, Kapton 150EN (all of which are polyimide films manufactured by Toray DuPont Co., Ltd.), and the Teonex series (polyethylene naphthalate films manufactured by Teijin Co., Ltd.).

[0023] The thickness of the base film 2 is not particularly limited and is, for example, 2 μm or more, preferably 10 μm or more, more preferably 20 μm or more, and for example, 500 μm or less, preferably 300 μm or less, more preferably 100 μm or less.

[0024] One surface in the thickness direction of the base film 2 may be subjected to treatment such as corona discharge treatment, ultraviolet irradiation treatment, plasma treatment, sputter etching treatment, etc., in order to improve adhesion with the resistance layer 3.

[0025] <Resistance layer> The resistive layer 3 is a layer that is patterned when the strain sensor 15 (see FIGS. 2A and 2B) is manufactured from the laminated film 1. The resistive layer 3 is disposed on one surface in the thickness direction of the base film 2. The resistive layer 3 forms one surface in the thickness direction of the laminated film 1. Specifically, the resistive layer 3 is in contact with the entire one surface in the thickness direction of the base film 2.

[0026] The resistive layer 3 includes chromium nitride. Specifically, the material of the resistive layer 3 contains chromium nitride as a main component. Meanwhile, the material of the resistive layer 3 is allowed to contain, for example, inevitable impurities. The proportion of the inevitable impurities in the resistive layer 3 is, for example, 1 atomic % or less, preferably 0.1 atomic % or less, and more preferably 0.05 atomic % or less. Preferably, the resistive layer 3 is made of chromium nitride.

[0027] In chromium nitride, the molar ratio of nitrogen atoms to 100 molar parts of chromium atoms is, for example, 1.0 molar part or more, and, for example, 10.0 molar parts or less. The molar ratio of nitrogen atoms to 100 molar parts of chromium atoms is measured by Rutherford backscattering spectrometry (RBS).

[0028] The thickness of the resistive layer 3 is 150 nm or less. On the other hand, if the thickness of the resistive layer 3 exceeds 150 nm, cracks are likely to occur in the resistive layer 3.

[0029] The thickness of the resistive layer 3 is preferably 100 nm or less, more preferably 90 nm or less, further preferably 80 nm or less, and for example, 10 nm or more, preferably 20 nm or more. If the thickness of the resistive layer 3 is equal to or greater than the above-mentioned lower limit, a high gauge factor can be ensured.

[0030] <Laminated film manufacturing method> In the method for producing the laminated film 1, for example, the laminated film 1 is formed by a roll-to-roll method.

[0031] First, in this method, for example, a long base film 2 is prepared. In this case, if the long direction is defined as the first direction and the width direction perpendicular to the long direction and the thickness direction is defined as the second direction, the absolute value of the thermal expansion coefficient of the base film 2 at 50 to 200°C in the first direction is, for example, 28 ppm / °C or less, preferably 20 ppm / °C or less, more preferably 15 ppm / °C or less, and for example, 1 ppm / °C or more. The absolute value of the thermal expansion coefficient of the base film 2 at 50 to 200°C in the second direction is, for example, 28 ppm / °C or less, preferably 15 ppm / °C or less, more preferably 10 ppm / °C or less, and for example, 0.5 ppm / °C or more.

[0032] Next, in this method, while conveying the long substrate film 2, the resistive layer 3 is formed on one surface in the thickness direction of the substrate film 2. Examples of the film formation method include sputtering, vacuum deposition, and ion plating. Preferably, sputtering is used, and more preferably, reactive sputtering is used.

[0033] In reactive sputtering, the target is made of chromium, and the sputtering gas is a mixture of an inert gas such as argon and nitrogen. The volumetric ratio of nitrogen to 100 volumetric parts of the inert gas is, for example, 0.5 to 15 volumetric parts.

[0034] In this way, a laminate film 1 including the base film 2 and the resistance layer 3 is produced.

[0035] Thereafter, if necessary, the laminated film 1 is heated in order to increase the crystallinity and improve the stability of the resistance layer 3. The heating temperature is not particularly limited and is, for example, 100° C. or more, preferably 125° C. or more, and for example, 200° C. or less, preferably 180° C. or less. The heating time is, for example, 1 minute or more, preferably 5 minutes or more, and for example, 3 hours or less, preferably 2 hours or less.

[0036] In this way, a laminate film 1 including the base film 2 and the resistance layer 3 is obtained.

[0037] The absolute values ​​of the dimensional change rates in the first and second directions of the laminated film 1 are both 0.025% or less. Since the absolute values ​​of the dimensional change rates in the first and second directions of the laminated film 1 are both 0.025% or less, fluctuations in the temperature resistance coefficient due to storage in a humid and hot environment are suppressed.

[0038] The absolute value of the dimensional change rate of the laminated film 1 in each of the first and second directions is preferably 0.020% or less, more preferably 0.010% or less, even more preferably 0.005% or less, and particularly preferably 0.003% or less, and, for example, exceeds 0.000%.

[0039] To determine the dimensional change rate of the laminated film 1 in each of the first and second directions, first prepare a sample by cutting the laminated film 1 to lengths of 18 mm and 5 mm in the first and second directions, respectively. Next, fix both ends of the sample in the first direction using a chuck jig so that the distance between them is 15 mm, and pull with a force of 49 mN / 5 mm for 4 hours in an atmosphere of 85°C and 85% RH. Measure the length of the sample in the first direction after pulling. Then, calculate the dimensional change rate in the first direction using the following formula. Using a similar method, measure the dimensional change rate in the second direction.

[0040] Dimensional change rate of the first direction length [%] = (first direction length of the sample after pulling - first direction length of the sample before pulling) / first direction length of the sample before pulling × 100

[0041] Dimensional change rate in the second direction length [%] = (length in the second direction of the sample after pulling - length in the second direction of the sample before pulling) / length in the second direction of the sample before pulling × 100

[0042] The difference in the temperature coefficient of resistance of the resistive layer 3 before and after storage for 240 hours at 85° C. and 85% RH is, for example, 100 ppm / ° C. or less, preferably 55 ppm / ° C. or less, more preferably 50 ppm / ° C. or less, even more preferably 35 ppm / ° C. or less, particularly preferably 30 ppm / ° C. or less, and for example, 1 ppm / ° C. or more. If the difference in the temperature coefficient of resistance before and after storage is the above-mentioned upper limit or less, the measurement accuracy of the strain sensor 15 is improved.

[0043] To determine the difference in the temperature coefficient of resistance before and after storage, after patterning the resistive layer 3, one side and the other side in the thickness direction of the laminated film 1 are fixed with glass plates, and they are stored in an atmosphere of 85°C and 85% RH for 240 hours. The difference in the temperature coefficient of resistance before and after storage is determined. Details of how to determine the difference in the temperature coefficient of resistance before and after storage will be described in the examples below.

[0044] <Manufacturing method of strain sensor> Next, a method for manufacturing the strain sensor 15 will be described with reference to FIGS. 2A and 2B.

[0045] 2A and 2B, in this manufacturing method, the resistive layer 3 in the laminated film 1 described above is patterned to form a resistive pattern 4. Examples of methods for patterning the resistive layer 3 include etching, and specific examples include dry etching and wet etching, preferably dry etching, and more preferably laser etching.

[0046] The resistance pattern 4 integrally includes a strain sensor portion 5, a terminal 6, and a wiring 7.

[0047] 2B, the strain sensor section 5 has a generally zigzag shape in a plan view. Specifically, the strain sensor section 5 has a plurality of first wires 8, a plurality of first connection wires 9, and a plurality of second connection wires 10.

[0048] Each of the multiple first lines 8 extends along a first direction. The multiple first lines 8 are aligned and spaced apart in the second direction.

[0049] The multiple first connection lines 9 connect one end in the first direction of the first lines 8 adjacent to each other in the second direction.

[0050] The second connection lines 10 connect the other ends in the first direction of the first lines 8 adjacent to each other in the second direction. When projected in the first direction, the first connection lines 9 and the second connection lines 10 are arranged alternately.

[0051] The terminal 6 is spaced apart in the surface direction from the strain sensor section 5. The terminal 6 has, for example, a land shape that is generally rectangular in plan view. Two terminals 6 are provided with a space therebetween.

[0052] The wiring 7 connects the two terminals 6 to both ends of the strain sensor unit 5 .

[0053] In the strain sensor section 5, one conductive path is formed from one terminal 6, passing through one wiring 7, the strain sensor section 5 and the other wiring 7, to the other terminal 6.

[0054] The dimensions of the strain sensor section 5 are appropriately set depending on the application and purpose. The widths of the first line 8, the first connection line 9 and the second connection line 10 are, for example, 1 μm or more, preferably 5 μm or more, more preferably 10 μm or more, and for example, 150 μm or less, preferably 100 μm or less, more preferably 70 μm or less.

[0055] The shape of the base film 2 is also appropriately set depending on the application and purpose of the strain sensor 15, and is formed into desired dimensions by, for example, outer shaping.

[0056] <Measurement of strain using a strain sensor> Next, a method of placing the strain sensor 15 on the object 20 and measuring the amount of strain (amount of deformation) of the object 20 will be described.

[0057] 2A, the laminated film 1 of the strain sensor 15 is attached to the surface of the specimen 20 via an adhesive layer 21. Furthermore, lead wires 23 are connected to the two terminals 6 via a conductive adhesive layer 22. The lead wires 23 are electrically connected to an external resistance measurement circuit (not shown).

[0058] When the object under test 20 is distorted, the resistance value of the strain sensor section 5 changes. Based on this, the amount of strain is calculated in the resistance measuring circuit.

[0059] Specifically, when the specimen 20 expands in the first direction, a tensile strain is applied to the first wire 8, the cross-sectional area of ​​the first wire 8 decreases, and the resistance of the strain sensor unit 5 increases. On the other hand, when the specimen 20 contracts, a compressive strain is applied to the first wire 8, the cross-sectional area of ​​the first wire 8 increases, and the resistance of the strain sensor unit 5 decreases. The amount of strain in the specimen 20 is calculated from such a change in resistance.

[0060] <Effects of the First Embodiment> In this laminated film 1, the absolute values ​​of the dimensional change rates of the laminated film 1 in both the first and second directions are 0.025% or less, so that the fluctuation of the temperature resistance coefficient due to storage in a humid and hot environment is suppressed. Also, in the laminated film 1, the thickness of the resistance layer 3 is 150 nm or less, so that the generation of cracks can be suppressed.

[0061] Moreover, according to the manufacturing method of the first embodiment, it is possible to manufacture the strain sensor 15 in which the variation in the temperature resistance coefficient due to storage in a humid and hot environment is suppressed, and the generation of cracks is suppressed.

[0062] <Modification of the first embodiment> In the first embodiment, the longitudinal direction (MD direction) produced by the roll-to-roll method is defined as the first direction, and the width direction (TD direction) is defined as the second direction, and the dimensional change rates in the first and second directions are obtained, but this is not limited thereto. Specifically, regardless of the production method of the laminated film 1, any one direction perpendicular to the thickness direction can be defined as the first direction, and the direction perpendicular thereto can be defined as the second direction, and the dimensional change rates in these directions can be obtained. The absolute values ​​of the dimensional change rates of the laminated film 1 in each of such first and second directions are also 0.025% or less.

[0063] <Second embodiment> In the second embodiment described below, the same reference numerals are used for the same components and steps as those in the first embodiment described above, and detailed descriptions thereof will be omitted. In addition, the second embodiment can achieve the same effects as those of the first embodiment, except as otherwise specified. Furthermore, the first embodiment and the second embodiment can be appropriately combined.

[0064] In the first embodiment, the dimensional change rate of the laminate film 1 is specified, but this is not limited to this, and in the second embodiment, the dimensional change rate of the base film 2 can be specified, as shown in Figure 3.

[0065] The base film 2 that is the subject of the dimensional change rate measurement is, specifically, a long base film 2 that is prepared first, as shown in FIG.

[0066] The absolute values ​​of the dimensional change rates in the first and second directions of this base film 2 after storage for 4 hours in an atmosphere of 85°C and 85% RH are both 0.040% or less. On the other hand, if the absolute value of the dimensional change rate in at least one of the first and second directions exceeds 0.040%, the fluctuation of the temperature resistance coefficient due to storage in a humid and hot environment is not suppressed.

[0067] The absolute value of the dimensional change rate of the base film 2 in each of the first direction and the second direction is preferably 0.020% or less, more preferably 0.010% or less, further preferably 0.005% or less, particularly preferably 0.004% or less, and for example, exceeds 0.000%. The dimensional change rate of the base film 2 is determined in the same manner as that of the laminate film 1.

[0068] When preparing a long base film 2, the longitudinal direction of the base film 2 is defined as the first direction, and the width direction is defined as the second direction. The dimensional change rate of the base film 2 in the first direction is, for example, 0.025% or less, more preferably 0.010% or less, even more preferably 0.005% or less, particularly preferably 0.004% or less, and for example, exceeds 0.000%. The dimensional change rate of the base film 2 in the second direction is, for example, 0.040% or less, more preferably 0.010% or less, even more preferably 0.007% or less, particularly preferably 0.005% or less, and for example, exceeds 0.000%.

[0069] The base film 2 prepared for manufacturing the laminated film 1 is not a base film 2 that has been stretched for 4 hours in an atmosphere of 85°C and 85% RH (high-temperature, high-humidity tensile test), but a base film 2 that has no history of the above-mentioned wet heat deformation (high-temperature, high-humidity tensile test) (so-called untreated). In other words, the above-mentioned high-temperature, high-humidity tensile test is a process necessary for measurement to determine the dimensional change rate, and is not a manufacturing process for the base film 2.

[0070] In the manufacturing method of the laminated film 1, a resistance layer 3 is formed on one thickness-wise surface of a base film 2 having the above-mentioned specific dimensional change rate in the same manner as in one embodiment, and heated if necessary, thereby obtaining the laminated film 1.

[0071] Thereafter, the resistance layer 3 of the laminated film 1 is patterned to form the strain sensor portion 5 .

[0072] <Effects of the Second Embodiment> In this laminated film 1, the absolute values ​​of the dimensional change rates of the base film 2 in both the first and second directions are 0.040% or less, so that the fluctuation of the temperature resistance coefficient due to storage in a humid and hot environment is suppressed. Also, in the laminated film 1, the thickness of the resistance layer 3 is 150 nm or less, so that the generation of cracks can be suppressed.

[0073] Moreover, according to the manufacturing method of the second embodiment, it is possible to manufacture the strain sensor 15 in which the variation in the temperature resistance coefficient due to storage in a humid and hot environment is suppressed and the generation of cracks is suppressed.

[0074] <Modification of the second embodiment> In the second embodiment, the dimensional change rate of the base film 2 before the laminate film 1 is manufactured is specified, but the dimensional change rate of the base film 2 after the laminate film 1 is manufactured and the resistance layer 3 in the laminate film 1 is removed may also be within the above range.

[0075] <Modifications of the First and Second Embodiments> The laminate film 1 may have a dimensional change rate that falls within the range of the first embodiment (0.025% or less), and the base film 2 may have a dimensional change rate that falls within the range of the second embodiment (0.040% or less).

[0076] Preferably, the dimensional change rate of the laminate film 1 satisfies the range of the first embodiment, and the dimensional change rate of the base film 2 satisfies the range of the second embodiment. This further suppresses the fluctuation of the temperature resistance coefficient due to storage in a humid and hot environment. EXAMPLES

[0077] The present invention will be described in more detail below with reference to examples and comparative examples. The present invention is not limited to the examples and comparative examples. The specific numerical values ​​of the blending ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters, etc. described in the above "Form for carrying out the invention".

[0078] Example 1 A base film 2 having a thickness of 50 μm and made of a polyimide film (Kapton 200V) manufactured by DuPont-Toray Co., Ltd. was prepared.

[0079] The substrate film 2 was set in the sputtering device. The vacuum level in the sputtering device was 1×10 -3 After evacuating the chamber to a pressure of 0.1 Pa or less, a resistive layer 3 made of chromium nitride was formed by reactive pulse DC sputtering (pulse width: 1 μs, frequency: 100 kHz) under the following conditions.

[0080] Target: Chrome, 500mm x 150mm flat plate Power: 5kW (power density: 6.7W / cm 2 ) Magnetic flux density (target surface): 30mT Substrate temperature: 150℃ Sputtering gas: Argon and nitrogen mixture Film forming pressure: 0.085Pa

[0081] The volume parts of nitrogen gas introduced into the sputtering apparatus relative to 100 volume parts of argon gas introduced into the sputtering apparatus was adjusted to be as shown in Table 1.

[0082] In this way, a long laminate film 1 including the base film 2 and the resistance layer 3 was produced.

[0083] The laminated film 1 was then heated (annealed) at 155° C. for 60 minutes.

[0084] Example 2 to Comparative Example 2 A laminate film 1 was produced in the same manner as in Example 1, except that the type of base film 2, the thickness of base film 2, the amount of nitrogen introduced during sputtering, the thickness of resistive layer 3, etc. were changed according to the descriptions in Table 1.

[0085] <Evaluation> The laminated film 1 of each of the Examples and Comparative Examples was measured for the following items. The results are shown in Table 1.

[0086] <Observation of the resistance layer> The resistance layer 3 was visually observed to check for the presence or absence of cracks.

[0087] <Thickness of the resistance layer> The laminated film 1 was treated by FIB microsampling so as to expose a cross section, and then the cross section was subjected to FE-TEM observation.

[0088] FIB equipment: Hitachi FB2200, Acceleration voltage: 40kV FE-TEM equipment: JEOL JEM-2800, accelerating voltage: 200kV

[0089] <Difference in temperature coefficient of resistance of resistive layer before and after storage at 85℃ and 85% RH for 240 hours> The laminated film 1 was cut to a size of 10 mm × 200 mm, and the resistive layer 3 was patterned by laser patterning into a zigzag shape with a width of 30 μm to produce the strain sensor 15. In this case, the patterning was adjusted so that the resistance of the wiring 7 was about 10 kΩ, and the resistance of the strain sensor part 5 was 30 times the resistance of the wiring 7.

[0090] A sample was prepared by bonding glass plates to both sides of the strain sensor 15 via an adhesive.

[0091] The temperature of the strain sensor part 5 of the sample was set to 5° C. A tester was connected to each of the two terminals 6, and the two-terminal resistance at 5° C. was measured by passing a constant current and reading the voltage. In the same manner, the two-terminal resistance at 25° C. and 45° C. was measured.

[0092] Then, the average value of the resistance temperature coefficient calculated from the resistance values ​​at 5° C. and 25° C. and the resistance temperature coefficient calculated from the resistance values ​​at 25° C. and 45° C. was obtained as the resistance temperature coefficient of the strain sensor portion 5 (resistance layer 3).

[0093] Separately, the above sample was stored at 85° C. and 85% RH for 240 hours. After storage, the resistance temperature coefficient of the strain sensor portion 5 of the sample was determined.

[0094] Then, the difference in the resistance temperature coefficient of the strain sensor portion 5 before and after storage was obtained.

[0095] <Dimensional change rate of laminated film and base film> A. Dimensional change rate of laminated film The long laminated film 1 was cut to a size of 15 mm x 5 mm to prepare a sample. The length of the sample, 15 mm, corresponded to the length in the longitudinal direction (first direction) (MD direction) of the laminated film 1. The width of the sample, 5 mm, corresponded to the length in the width direction (second direction) (TD direction) of the laminated film 1.

[0096] The sample was set in a thermomechanical analyzer (TMA 4000SE, manufactured by Netsch Japan). Specifically, one end and the other end of the sample in the longitudinal direction were held by a chuck. The measurement chamber was set to 85°C and 85% RH. The sample was pulled with a force of 49 mN / 5 mm for 4 hours.

[0097] Thereafter, the rate of dimensional change in each of the length direction and width direction of the laminated film 1 before and after the stretching was determined.

[0098] B. Dimensional change rate of the base film The base film 2 before the formation of the resistance layer 3 was also subjected to the same procedure as above to determine the rate of dimensional change in each of the length direction and width direction of the base film 2 before and after storage.

[0099] <Thermal expansion coefficient of base film> The thermal expansion coefficient of the base film 2 was measured in accordance with JIS K 7197 (1991) using the following device and conditions.

[0100] Equipment: SII NanoTechnology TMA / SS7100 Measurement mode: Tensile method Measurement load: 19.6mN Temperature range: 25℃~155℃ Heating rate: 10℃ / min Measurement atmosphere: Atmosphere (air)

[0101] <Heat shrinkage rate of base film> The heat shrinkage rate of the base film 2 at 200° C. was measured according to the description in JIS K 7133 (1999).

[0102] [Table 1] [Explanation of symbols]

[0103] 1. Laminated film 2. Base film 3 resistance layer 5 Sensor section 15 Strain Sensor

Claims

1. A laminated film including an insulating base film and a resistive layer in that order in a thickness direction, the base film is polyimide or polyethylene naphthalate, the resistive layer is made of chromium nitride or made of chromium nitride and unavoidable impurities; The thickness of the resistive layer is 150 nm or less, The laminated film is cut to prepare a sample so that the lengths in a first direction and a second direction which are perpendicular to the thickness direction and perpendicular to each other are 15 mm and 5 mm, respectively, and after pulling both ends of the sample in the first direction with a force of 49 mN / 5 mm for 4 hours in an atmosphere of 85°C and 85% RH, the absolute values ​​of the dimensional change rates in each of the first direction and the second direction are both 0.025% or less.

2. The insulating base film and the resistive layer are provided in that order in the thickness direction. the base film is polyimide or polyethylene naphthalate, the resistive layer is made of chromium nitride or made of chromium nitride and unavoidable impurities; The thickness of the resistive layer is 150 nm or less, A laminated film, characterized in that a sample is prepared by cutting the base film to have lengths of 15 mm and 5 mm in a first direction and a second direction that are perpendicular to the thickness direction and perpendicular to each other, and after pulling both ends of the sample in the first direction with a force of 49 mN / 5 mm for 4 hours in an atmosphere of 85°C and 85% RH, the absolute values ​​of the dimensional change rates in each of the first direction and the second direction are both 0.040% or less.

3. A method for producing a strain sensor, comprising patterning the resistive layer in the laminated film according to claim 1 or 2 to form a strain sensor portion.

Citation Information

Patent Citations

  • Strain gage

    JP1991122504A

  • Cr-n-based strained resistance film, manufacture therefor and strain sensor

    JP1998270201A

  • Laminated thin film electric wiring board

    JP2006147812A

  • Strain gage

    JP2014074661A

  • Strain sensor

    JP2015031633A